Continuous biosorption of acid red 27 azo dye by Eichhornia crassipes leaves in a packed-bed column - Allan Eduardo Ramírez-Rodríguez (Nature Portfolio, 2021)
Abstract In this work, the biosorption behavior of acid red 27 (AR27) dye using Eichhornia crassipes leaves (LECs) in a packed-bed column was investigated by varying relevant operational parameters and assessment of mathematical models. Results showed that the zero-charge point of LECs was 2.37 and that optima pH and volumetric flux of the influent solution for AR27 biosorption were 2.0 and $$56.5\ \hbox {L}/\hbox {m}^{2}\cdot \hbox {h}$$ 56.5 L / m 2 · h , respectively. The maximum specific and volumetric biosorption capacities were observed at influent AR27 concentrations and with LEC bed heights ranging between 50 and 400 mg/L and 2 and 8 cm, respectively. It was also found that if LEC bed height was increased and volumetric flux and AR27 concentration of the influent solution decreased, service and saturation time increased. Modeling results revealed that the Thomas, bed depth service time, Yoon–Nelson, dose-response, and logistic models accurately described the dynamic performance of the packed-bed column in terms of pH, AR27 concentration, and volumetric flux of influent AR27 solution, as well as that of LEC bed height. The findings revealed that LECs exhibited remarkable potential for the biosorption of AR27 from aqueous solutions in a packed-bed column and could potentially be useful for the treatment of AR27-laden wastewater.